Retracted: Addition of a single methyl group to a small molecule sodium channel inhibitor introduces a new mode of gating modulation. (15th October 2015) - Wang, Lingxin; Zellmer, Shannon G.; Printzenhoff, David M.; Castle, Neil A.
Abstract : Background and Purpose: Aryl sulfonamide Nav 1.3 or Nav 1.7 voltage‐gated sodium (Nav ) channel inhibitors interact with the Domain 4 voltage sensor domain (D4 VSD). During studies to better understand the structure‐activity relationship of this interaction, an additional mode of channel modulation, specifically slowing of inactivation, was revealed by addition of a single methyl moiety. The objective of the current study was to determine if these different modulatory effects are mediated by the same or distinct interactions with the channel. Experimental Approach: Electrophysiology and site‐directed mutation were used to compare the effects of PF‐06526290 and its desmethyl analogue PF‐05661014 on Nav channel function. Key Results: PF‐05661014 selectively inhibits Nav 1.3 versus Nav 1.7 currents by stabilizing inactivated channels via interaction with D4 VSD. In contrast, PF‐06526290, which differs from PF‐05661014 by a single methyl group, exhibits a dual effect. It greatly slows inactivation of Nav channels in a subtype‐independent manner. However, upon prolonged depolarization to induce inactivation, PF‐06526290 becomes a Nav subtype selective inhibitor similar to PF‐05661014. Mutation of the D4 VSD modulates inhibition of Nav 1.3 or Nav 1.7 by both PF‐05661014 and PF‐06526290, but has no effect on the inactivation slowing produced by PF‐06526290. This finding, along with the absence of functional inhibition of PF‐06526290‐induced inactivation slowing by PF‐05661014, suggests that distinct interactions underlie the two modes of Nav channel modulation. Conclusions and Implications: Addition of a methyl group to a Nav channel inhibitor introduces an additional mode of gating modulation, implying that a single compound can affect sodium channel function in multiple ways.